Corrosion behaviour analysis of galvanised steel in severe marine and extremely cold climatic conditions - Yanqi Yang; Chuan Wang; Yuwei Liu; Tianzhen Gu; Quanzhong Guo; Gongwang Cao (Corrosion Engineering, Science and Technology: The International Journal of Corrosion Processes and Corrosion Control, 2025)
The corrosion mechanism of galvanised steel (GS) was systematically compared under the Wanning marine atmosphere and the Mohe extremely cold conditions through corrosion rate analysis, morphological observations, corrosion product analysis, and electrochemical measurements. The findings demonstrate a significant environmental influence on GS corrosion behaviour. GS exhibited significantly higher corrosion rates in the Wanning marine environment than in the Mohe extremely cold environment. In the Wanning marine environment, the corrosion product layer undergoes progressively densifying over time, thereby enhancing the corrosion barrier effectiveness of the zinc coating. The electrochemical migration of Cl − in marine environments promotes its adsorption onto the coating surface, subsequent dissolution, and enhanced ionic conductivity within the electrolyte film. Following 36-month exposure, Cl − infiltration through the coating initiated microstructural collapse, with subsequent corrosion rate manifesting a distinctive V-shaped trajectory, it reached a minimum value of 3.357 g·m −2 ·a −1 at the 24-month then increased rapidly to 26.089 g·m −2 ·a −1 at the 36-month. In contrast, the prevailing low temperatures in Mohe induced the progressive densification of the corrosion product layer over time, which acted as an enhanced protective barrier for GS and mitigated corrosion progression. The corrosion rate reached a minimum value of 2.286 g·m −2 ·a −1 at the 36-month of exposure.